Two approaches to estimating public expenditures - Werner Pommerehne; Bruno S. Frey (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1975)
Traditionally, the demand for public expenditures has been estimated using as explanatory variables the average values of per capita income, as well as other variables. The results of this approach are disappointing which is due to the lacking theoretical basis. The public choice model, on the other hand, uses the political decision-making process (median voter model) to explain expenditures. Taking the same set of data, it is shown that the public choice approach yields superior results. It also offers a solution to the unfruitful discussion about the influence of political determinants of public expenditures.
Keywords: 330